Auditoría de gestión y su relación con la toma de decisiones del departamento de talento humano del gobierno autónomo descentralizado municipal del cantón Mocache, año 2012. - Espinoza Veloz, Carmen Mercedes (2015)
This research project in their overall context, a detailed analysis of all aspects related to Auditing, decision making and job performance benchmark Talent Municipal Government Autonomous Decentralized Mocache Canton, in order to evaluate alternative improvement, to guide managers of the institution, to foster a pleasant work environment and motivating for Talent, and thus develop a good job performance. This research yielded information relevant aspects of the institution, through the general objective and specific activities needed was undertaken to carry out the planning, execution and reporting of results, also applying appropriate indicators, giving results Human Resource Department is deficient because it does not have a manual functions, continue training, improper staffing, how it was also verified that they are not fully complying with the rules and procedure. In addition to a good performance of human talent is essential to provide methods, techniques or procedures, which help encourage become proficient among coworkers, creating a mature behavior around the human talent, allowing them to undertake to be responsible for their assignments labor ensuring efficiency, effectiveness and excellence in activities. With these parameters the findings according to the specific objectives is encouraged, taking into account the human talent plays a leading role in the development of the institution, which must be trained, evaluated and provide a level of compliance with the rules and procedures; All this leads to determine providing recommendations from a point of view to the audited profit institution.